Pendampingan Manajemen SDM untuk Optimalisasi Kinerja Guru dan Staf Sekolah - Moh Usman Kurniawan; Neviyani Neviyani; Noviana Mariatul Ulfa; Denok Mugi Hidayanti (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
The community service activity titled "Human Resource Management Assistance for Optimizing Teacher and Staff Performance" aims to improve the management of human resources (HR) at the Islamic Integrated Elementary School (SDIT) in Kencong District, Jember Regency. This assistance focused on enhancing skills in planning, performance evaluation, and the use of technology for administration. The measurement results obtained through questionnaires, interviews, and observations show significant positive impacts. The questionnaire indicated an increase in scores regarding HR management understanding, the application of performance evaluations, and administrative efficiency, which improved by up to 90%. Interviews with teachers, staff, and the principal highlighted that the activity helped improve coordination and the use of technology in administration. Observations also noted improvements in the organization and efficiency of work planning structures. Overall, this activity successfully enhanced the performance of teachers and staff by introducing more structured and technology-based HR management. These improvements are expected to have long-term impacts, both on the quality of education and HR management at the school. The success of this initiative not only affects the effectiveness of work at the school but also serves as a model that other schools can adopt to improve HR management and overall educational quality.